D-Dimer in African Americans: Whole Genome Sequence Analysis and Relationship to Cardiovascular Disease Risk in the Jackson Heart Study. Issue 11 (November 2017) - Raffield, Laura M.; Zakai, Neil A.; Duan, Qing; Laurie, Cecelia; Smith, Joshua D.; Irvin, Marguerite R.; Doyle, Margaret F.; Naik, Rakhi P.; Song, Ci; Manichaikul, Ani W.; Liu, Yongmei; Durda, Peter; et al.
Abstract : Objective—: Plasma levels of the fibrinogen degradation product D-dimer are higher among African Americans (AAs) compared with those of European ancestry and higher among women compared with men. Among AAs, little is known of the genetic architecture of D-dimer or the relationship of D-dimer to incident cardiovascular disease. Approach and Results—: We measured baseline D-dimer in 4163 AAs aged 21 to 93 years from the prospective JHS (Jackson Heart Study) cohort and assessed association with incident cardiovascular disease events. In participants with whole genome sequencing data (n=2980), we evaluated common and rare genetic variants for association with D-dimer. Each standard deviation higher baseline D-dimer was associated with a 20% to 30% increased hazard for incident coronary heart disease, stroke, and all-cause mortality. Genetic variation near F3 was associated with higher D-dimer (rs2022030, β=0.284, P =3.24×10 –11 ). The rs2022030 effect size was nearly 3× larger among women (β=0.373, P =9.06×10 –13 ) than among men (β=0.135, P =0.06; P interaction =0.009). The sex by rs2022030 interaction was replicated in an independent sample of 10 808 multiethnic men and women ( P interaction =0.001). Finally, the African ancestral sickle cell variant ( HBB rs334) was significantly associated with higher D-dimer in JHS (β=0.507, P =1.41×10 –14 ), and this association was successfully replicated in 1933 AAs ( P =2.3×10 –5 ). Conclusions—: These results highlight D-dimer as an important predictor of cardiovascular disease risk in AAs and suggest that sex-specific and African ancestral genetic effects of the F3 and HBB loci contribute to the higher levels of D-dimer among women and AAs. Abstract : Supplemental Digital Content is available in the text.